Structural insights into the substrate uptake and inhibition of the human creatine transporter (hCRT) - Xinyi Yuan; Jian Yin; Chang Liu; Xudong Chen; Meiying Chen; Yixue Wang; Zi Yang; Yue Wang; Li Jiang; Niyun Zhou; Xiaojuan Wang; Botong Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Creatine plays a vital role in cellular energy production and adenosine triphosphate (ATP) homeostasis and has also been identified as a neurotransmitter in the mammalian brain. Creatine is transported into cells by the human creatine transporter (hCRT) (SLC6A8), an Na + /Cl − -dependent symporter encoded on the X chromosome. Mutations in hCRT cause cerebral creatine deficiency syndrome 1, a neurological disorder marked by intellectual disability, speech delay, and seizures. Beyond its role in the brain and muscle, hCRT is highly expressed in metabolically active tumors. Many cancer cells, including colorectal cancer and glioblastoma, upregulate hCRT to sustain intracellular creatine levels and buffer ATP under energy stress. Pharmacological blockade of hCRT by RGX202 has been shown to impair tumor growth by disrupting energy homeostasis. Here, we report the high-resolution cryo-Electron Microscopy (cryo-EM) structures of human hCRT in three states: apo, creatine-bound, and RGX202-bound. hCRT adopts a canonical LeuT-fold with 12 transmembrane helices and two pseudosymmetric inverted repeats. Creatine is coordinated in the central substrate-binding site through interactions with transmembrane helices TM1, TM3, TM6, and TM8, while the inhibitor RGX202 occupies the same binding pocket, engaging in overlapping contacts that competitively block creatine access. Our structural and mechanistic findings clarify substrate recognition and inhibitory binding of hCRT, providing a molecular rationale for targeting hCRT in both inherited metabolic diseases and cancer therapy.